Analysisreliability Of Aircraft Electrical And Pneumatic Monitoring On Boeing 737 Aircraft - Faisal Arrasyid Pulungan; Siti Anisah; Haris Gunawan (Jurnal Scientia, 2024)
This study analyzes the reliability of the electrical and pneumatic monitoring system on the Boeing 737 aircraft, which is a critical component in ensuring the safety and operational efficiency of the aircraft. The electrical system is responsible for supporting various vital functions of the aircraft, such as navigation, communication, and flight control, while the pneumatic system regulates airflow for various subsystems, including the anti-icing system, cabin control, and hydraulic pressure. The purpose of this study is to evaluate the performance of the monitoring system in detecting disturbances or failures in electrical and pneumatic components. The approach used involves direct monitoring, historical data collection, and predictive analysis using statistical methods to assess the level of system reliability. The results of the study indicate that the Boeing 737 monitoring system has high reliability in detecting problems before they become critical, but there are several aspects that need improvement, especially in terms of early detection of failures in the pneumatic system. Improving the reliability of the monitoring system can be done through the integration of more sophisticated sensor technology and artificial intelligence (AI)-based predictive algorithms. Thus, these improvements can improve the operational safety and efficiency of the aircraft.